Ejes estructurantes. propuesta de intervención urbana en el sector norte de Riobamba - Dávila Arteaga, Winston Eduardo (2023)
In the environment of accelerated urban growth, the challenges that contemporary cities face, such as the revitalization of urban areas and the proper planning of growing urban areas, have become a crucial priority to achieve optimal development with an improved quality of life for their inhabitants. In the same way, the renovation and correct intervention of the structuring axes emerges as a critical strategy to intervene in one of the starting points that cause the most problems at the city level. These axes represent vital arteries that connect and cross various sectors, also called urban polygons, and play a fundamental role in the urban fabric, mobility, commerce, and community life. This study focuses on a macro, meso, and micro-urban analysis of the city of Riobamba, allowing us to understand the problems of territorial, urban, and immediate context formation, respectively, thus presenting an intervention proposal for the revitalization of the northern area of the city, which, due to its history, has the potential for a subtle intervention in abandoned or unconsolidated sites. This is how this place has been affected by an economic decline, the lack of investment, and the deterioration of its infrastructure. Finally, this study aims to contribute to the enrichment of the reactivation and renovation of some urban regions starting from their fundamental bases, such as the structural axes, used in such a way that they become critical tools for a positive change in degraded or unconsolidated urban areas. The results can serve as a valuable resource for future urban policy decisions, significantly improving the quality of life of the Riobamba population who pass through these areas.